How can we improve information for people affected by cancer? A national survey exploring gaps in current information provision, and challenges with accessing cancer information online. Issue 8 (August 2022) - Hyatt, Amelia; Shelly, Amy; Cox, Raylene; Humphries, Elizabeth; Lock, Gemma; Varlow, Megan
Abstract: Objective: Despite improved recognition regarding the importance and association between provision of high quality information for people affected by cancer and improved outcomes and experiences; gaps and unmet needs are still reported. As oncology health information provision increasingly moves online, understanding how service users experience and manage misinformation is important. Determining patient and carer preferences regarding cancer provision is needed to address outstanding gaps. Methods: This study utilised a purpose-built national cross-sectional survey distributed via social media to assess perspectives regarding cancer information in Australia. Quantitative and qualitative (open text) items assessed respondents' perspectives regarding current inforation preferences and gaps, and experiences with accessing information online. Results: A total of 491 people affected by cancer completed the survey. Respondents highlighted a preference for information that better addresses the diversity of cancer experience, and is more timely and responsive to personal situation and care context. Despite increasing attention to health literacy standards, complex medical jargon and terminology remains prevalent. Many respondents have concerns about misinformation, and seek improved mechanisms or skills to assist with determining the trustworthiness and relevance of information found online. Conclusions: Survey responses identified current gaps in information provision for people affected by cancer. Personalised information in formats which are more flexible, accessible, and responsive to user needs are required. Practice Implications: Education and resources to target and improve digital health literacy and combat health misinformation are needed. Novel solutions co-designed by people affected by cancer will ensure that information is provided in a manner that is relevant, timely, and personalised. Highlights: Information needs of people affected by cancer are varied and change over time. Cancer information should better facilitate customisation and personalisation. Different ways to proactively share cancer information must be developed. Resources to improve digital health literacy and combat misinformation are needed.